Comparative genomic analysis identifies structural features of CRISPR-Cas systems in Riemerella anatipestifer. (December 2016) - Zhu, De-Kang; Yang, Xue-Qin; He, Yang; Zhou, Wang-Shu; Song, Xiao-Heng; Wang, Jiang-Bo; Zhang, Yu; Liu, Ma-Feng; Wang, Ming-Shu; Jia, Ren-Yong; Chen, Shun; Sun, Kun-Feng; et al.
Abstract Background Riemerella anatipestifer infection is a contagious disease that has resulted in major economic losses in the duck industry worldwide. This study attempted to characterize CRISPR-Cas systems in the disease-causing agent, Riemerella anatipestifer (R. anatipestifer ). The CRISPR-Cas system provides adaptive immunity against foreign genetic elements in prokaryotes and CRISPR-cas loci extensively exist in the genomes of archaea and bacteria. However, the structure characteristics ofR. anatipestifer CRISPR-Cas systems remains to be elucidated due to the limited availability of genomic data. Results To identify the structure and components associated with CRISPR-Cas systems inR. anatipestifer, we performed comparative genomic analysis of CRISPR-Cas systems in 25R. anatipestifer strains using high-throughput sequencing. The results showed that most of theR. anatipestifer strains (20/25) that were analyzed have two CRISPR loci (CRISPR1 and CRISPR2). CRISPR1 was shown to be flanked on one side bycas genes, while CRISPR2 was designated as an orphan. The other analyzed strains harbored only one locus, either CRISPR1 or CRISPR2. The length and content of consensus direct repeat sequences, as well as the length of spacer sequences associated with the two loci, differed from each other. Only threecas genes (cas1, cas2 andcas9 ) were located upstream of CRISPR1. CRISPR1 was also shown to be flanked by a 107 bp-long putative leader sequence and a 16 nt-long anti-repeat sequence. Combined with analysis of spacer organization similarity and phylogenetic tree of theR. anatipestifer strains, CRISPR arrays can be divided into different subgroups. The diversity of spacer organization was observed in the same subgroup. In general, spacer organization in CRISPR1 was more divergent than that in CRISPR2. Additionally, only 8 % of spacers (13/153) were homologous with phage or plasmid sequences. Thecas operon flanking CRISPR1 was observed to be relatively conserved based on multiple sequence alignments of Cas amino acid sequences. The phylogenetic analysis associated with Cas9 showed Cas9 sequence fromR. anatipestifer was closely related to that ofBacteroides fragilis and formed part of the subtype II-C subcluster. Conclusions Our data revealed for the first time the structural features ofR. anatipestifer CRISPR-Cas systems. The illumination of structural features of CRISPR-Cas system may assist in studying the specific mechanism associated with CRISPR-mediated adaptive immunity and other biological functions inR. anatipestifer .